Analysis of the thermal efficiency of a compound parabolic Integrated Collector Storage solar water heater in Kerman, Iran. (December 2019) - Panahi, Rashid; Khanjanpour, Mohammad Hassan; Javadi, Akbar A.; Akrami, Mohammad; Rahnama, Mohammad; Ameri, Mehran
Abstract: This paper presents an experimental study involving the design, manufacturing and testing of a prototype integrated collector storage (ICS) solar water heater (SWH) in combination with a compound parabolic concentrator (CPC). The thermal efficiency of the developed system is evaluated in Kerman (latitude 30.2907° N, longitude 57.0679° E), Iran. The developed system is intended to supply hot water for a family in remote rural areas. A 6-month experimental study was undertaken to investigate the performance of the ICS SWH system. The mean daily efficiency and overnight thermal loss coefficient of each experiment were analyzed to examine the appropriateness of these collectors for regions in Kerman. The results showed that mirror has the highest mean daily efficiency (66.7%), followed by steel sheet (47.6%) and aluminum foil (43.7%). The analysis of hourly and monthly operation diagrams for variations of water temperature for the developed ICS system showed that by increasing the amount of radiation entering the water heater, the thermal efficiency of the system decreases, such that the highest efficiency was in April and the lowest in July. With the distribution of radiation intensity in the months of August and September, the thermal efficiency of the system increased. This regional study illustrates how selecting a proper concentrator can increase the thermal efficiency of this solar-based system. It also shows how the temperature gradient between the ambient air and internal water in the storage tank can influence the performance of such systems, and how a controlled amount of hot water withdrawal can affect the system's efficiency. Developing the ICSSWH system is an ideal sustainable solution in countries that benefit from a large amount of solar intensity.